«ANA TILI HÁM OQÍW SAWATLÍLÍǴÍ» VA «АНА ТІЛІ ЖӘНЕ ОҚУ САУАТТЫЛЫҒЫ» DARSLIKLARI ASOSIDA O‘QUVCHILAR SO‘Z BOYLIGINI OSHIRISH - Tuzikenova, J.A. (SCIENCE and SOCIETY, 2024)
The article discusses the issue of the formation of lexical competence of students based on textbooks “Native language and reading literacy” of Karakalpak and Kazakh-speaking primary schools.
Keywords: word; word meaning; vocabulary; textbook; oral and written speech; listening comprehension and reading